PROBLEMS OF MODERNIZATION OF THE RESTAURANT INDUSTRY IN TRANSCARPATHIA (Development Service Industry Management, 2024)
The article is devoted to the study of current problems and prospects of modernization of the restaurant industry of the Transcarpathian region in the context of its competitiveness and attractiveness for investors. The paper analyzes the current state of the industry, its development in the context of global trends in hospitality and sustainable tourism. It has been determined that the region, known for its natural beauty and rich cultural heritage, has significant potential for the development of the restaurant business based on the use of local products, authentic recipes and innovative technologies. The industry's main challenges include economic instability, declining consumer demand, the impact of the COVID-19 pandemic and the aftermath of military operations. The article notes the tendency to reduce the number of restaurant establishments in Transcarpathia over the past decade. Particular attention is paid to the staffing problems that have arisen as a result of the mobilization of workers, the outflow of skilled personnel, and the decline in demand for food services. At the same time, the article notes the positive dynamics of the restaurant business recovery after the crisis. In 2023, the region saw the opening of new establishments, particularly in the regional center of Uzhhorod, which indicates a growing confidence of entrepreneurs in the industry's prospects. New establishments are actively implementing innovative technologies, including interactive services, environmentally friendly products, process automation and personalized service, which improves the quality of services and promotes the development of gastronomic tourism. The article analyzes the activities of the leading restaurants in the region that use modern technologies to ensure competitive advantages. In particular, interactive services, automated ordering systems, environmental initiatives, and other innovations that have a positive impact on the attractiveness of establishments for both locals and tourists are studied. The article concludes that the modernization of the restaurant industry in Zakarpattia is an important factor in increasing the region's tourist attractiveness. Recommendations for the further development of the industry by expanding the use of innovative technologies, supporting local production and attracting investment are proposed. This will help create new jobs, increase local budget revenues and strengthen Zakarpattia's position as a leading tourist destination in Ukraine.
Keywords: modernization of the restaurant industry; competitiveness; innovative technologies; sustainable development; environmental sustainability; local products; tourist attractiveness; human resources; economic challenges